Canopy flow and aspects of the response of plants protected by herbaceous shelterbelts and wood fences - Boldes, Ulfilas (2002)
Field experiments have been conducted in the semiarid southwest region of La Pampa, Argentina, in order to investigate the effect of different types of windbreak on wind characteristics and growth parameters of wheat (Triticum aestivum, Buck Charrua variety) within the sheltered region. Windbreaks decrease wind speed, reducing damage to the crop and improving yield and quality. Sheltering may improve microclimate conditions for plant growth and protects the soil from wind erosion. Aspects of the sheltering ability of four different windbreaks have been tested: single and double row herbaceous (Tritio secale) shelterbelts, and two different artificial wooden fences, with the same overall average porosity, but with different porosity distributions. Mean velocity, turbulence intensity, skewness distributions and spectral and wavelet analysis have been performed in order to characterise the turbulent flow downstream of the different windbreaks. Wheat grain yield and harvest index were compared with adjacent unsheltered plantations. The single and double row shelterbelts enhanced the grain yield and the harvest index of the protected plants. An influence of the turbulent structure on plant growth is suggested by the different response of plants sheltered by the two types of artificial fences.